A Comparative Study of The Results of Conventional Surgery and Diode Laser in Maxillary Labial Frenectomy: A Randomized Clinical Trial - Yousefimanesh, Hojatollah; Salehi, Parvin; Maraghi, Elham; Johari, Dariush (Galen Medical Journal, 2024)
Background: The frenum, a flexible tissue structure connecting the lips, tongue, and cheeks to the gingiva, can exhibit abnormalities leading to dental complications such as diastema and restricted movement. This study investigates the efficacy and safety of frenectomy by diode laser, compared to traditional surgical approaches. Materials and Methods: This clinical trial, approved by the ethical committee and registered with the Iranian Registry of Clinical Trials (IRCT20231009059673N1), enrolled 26 patients requiring maxillary labial frenectomy due to papillary or penetrating frenum types who had referred to specialized periodontics department of Jundishapur Dental School of Ahvaz in 2023-2024. Participants were randomly assigned to either a conventional surgical method or the frenectomy by diode laser (Quicklase laser, UK). Surgical procedures were standardized, and various outcome measures—including surgery duration, pain assessment, surgical difficulty, bleeding intensity, swelling, and tissue repair were evaluated and compared among groups. Results: This study evaluated the outcomes of maxillary labial frenectomy using laser versus conventional methods in 26 participants (19 women, 7 men). Significant differences were found in surgery duration (laser: 341.46 seconds vs. conventional: 675.00 seconds, P < 0.001) and pain levels, with the laser group reporting lower pain on Days One (3.53 vs. 6.00, P < 0.001) and Seven (0.46 vs. 1.38, P = 0.002). The laser group also experienced less bleeding and swelling, higher healing scores at one week (3.92 vs. 2.61, P < 0.001), and required fewer analgesics (5.53 vs. 9.76, P < 0.001), demonstrating superior outcomes with laser treatment. Conclusion: In conclusion, the England Quicklase laser method demonstrates significant advantages over conventional frenectomy techniques, including shorter surgery duration, reduced pain and bleeding, improved healing, and lower analgesic use. These findings support the laser’s potential as a preferred option for maxillary labial frenectomy, enhancing patient care.